Blockage of High-Affinity Choline Transporter Increases Visceral Hypersensitivity in Rats with Chronic Stress - Chen Zhao; Mengjuan Lin; Yasi Pan; Baoping Yu (Gastroenterology Research and Practice)
Background. Visceral hypersensitivity is a common feature of irritable bowel syndrome. Cholinergic system involves in the development of visceral hypersensitivity, and high-affinity choline transporter (CHT1) is of crucial importance in choline uptake system. However, involvement of CHT1 in visceral hypersensitivity remains unknown. The research aimed to study the CHT1 expression in dorsal root ganglions (DRGs) and the role of CHT1 in visceral hypersensitivity. Methods. Repetitive water avoidance stress (WAS) was used to induce visceral hypersensitivity in rats. Colorectal distension (CRD) was determined, and the abdominal withdrawal reflex (AWR) and threshold intensity data were recorded to measure the visceral sensitivity. After intraperitoneal injection of hemicholinium-3 (HC-3), the specific inhibitor of CHT1, CRD data were also recorded. The CHT1 expression of DRGs was investigated by Western blotting, immunohistochemistry, and quantitative RT-PCR. Acetylcholine levels in the DRGs were detected by the assay kit. Results. Repetitive WAS increased the AWR score of CRD at high distension pressure and decreased the mean threshold of rats. The CHT1 expression and acetylcholine concentration of DRG were significantly increased in WAS rats. After the administration of HC-3, the AWR score in WAS group was significantly increased at higher distension pressure while the threshold intensity was significantly reduced compared to the normal saline group. Acetylcholine concentration was significantly lower than the normal saline rats. Conclusion. Our research firstly reports that CHT1 is overexpressed in noninflammatory visceral hypersensitivity, and blockage of CHT1 can enhance the visceral hypersensitivity. CHT1 may play an inhibitory role in visceral hypersensitivity.